Community Participation and Involement in Social Actions - Teodor Mircea ALEXIU; Theofild-Andrei LAZĂR; Elena-Loreni BACIU (Transylvanian Review of Administrative Sciences, 2011)
The article explores the topic of community participation as means not only for an efficient use of resources, but also as an instrument for increasing social solidarity, especially among citizens of rural communities, deprived of access to services that usually the inhabitants of urban communities take for “granted”. In an era of decentralization, where the delivery of services (especially social services) is based on the subsidiarity principle, community members have to rely more on themselves and their neighbors, than on the help from the state. The paper also presents the results of a study developed in two rural communities from Timiş County, Romania. The study approaches the connection between community participation and involvement in social actions under three dimensions of the community: the remoteness of the village from a major city, the extent of the first level of community participation, and the level of social involvement. The findings about the relationship between community participation and involvement in social actions show another type of connection then the initial hypothesis. Some possible explanations about these findings are presented in this article.